1969
DOI: 10.1159/000468850
|View full text |Cite
|
Sign up to set email alerts
|

The Secretion of Lithium in Human Mixed Saliva: Effects of Ingested Lithium on Electrolyte Distribution in Saliva and Serum

Abstract: Outlining some of the more salient findings of this investigation: 1. Lithium appears in both saliva and serum without showing any appreciable time transient (found in saliva as early as one hour after administration). 2. Lithium is present in saliva at concentrations approximately two times that found in serum, this ratio holding in different diagnostic categories and over a wide range of dosages. 3. A concentration gradient obtained between saliva-serum lithium suggests an alternative method for determining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

1971
1971
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…The inverse as sociation demonstrated between the Li content of saliva and flow rate is in ac cordance with the findings of Spring and Spines [1969] for subjects receiving short term Li therapy and with those of Scham schula et al [1978] for untreated subjects. In early studies in dogs [Burgen, 1958], cats [Good, 1903] and in a more recent study of humans [Shopsin et al, 1969], in which large quantities of Li were adminis tered, the corresponding associations were conflicting and inconclusive. We are not aware of previous studies concerned with the relationship between the buffering ca pacity and Li content of saliva.…”
Section: Discussionmentioning
confidence: 99%
“…The inverse as sociation demonstrated between the Li content of saliva and flow rate is in ac cordance with the findings of Spring and Spines [1969] for subjects receiving short term Li therapy and with those of Scham schula et al [1978] for untreated subjects. In early studies in dogs [Burgen, 1958], cats [Good, 1903] and in a more recent study of humans [Shopsin et al, 1969], in which large quantities of Li were adminis tered, the corresponding associations were conflicting and inconclusive. We are not aware of previous studies concerned with the relationship between the buffering ca pacity and Li content of saliva.…”
Section: Discussionmentioning
confidence: 99%
“…Lithium excretion in saliva appears to be an active process resembling that of potassium excretion in saliva and is not markedly influenced by dietary regimens. 5 On the other hand, lithium excretion in urine appears to be a passive process resembling that of sodium excretion in the proximal tubule, which is affected by posture-induced changes in glomerular filtration rate but not by urine flow rate and is also influenced by dietary regimens. 7 • 9.…”
Section: Discussionmentioning
confidence: 99%
“…17 Another report suggested that lithium levels in the serum are directly proportional to the severity of sialorrhoea. 22 Lithium levels affect the catecholamine metabolism in the central nervous system but have no effects on the peripheral nervous system. 22,23,26,27 The secretion of lithium ions in the saliva is known to cause persistent localized irritation.…”
Section: Lithium-induced Sialorrhoeamentioning
confidence: 99%